Positioning Fisheries in a Changing World - Grafton, R. Q. (2012)
Marine capture fisheries face major and complex challenges: habitat degradation, poor economic returns, social hardships from depleted stocks, illegal fishing, and climate change, among others. The key factors that prevent the transition to sustainable fisheries are information failures, transition costs, use and non-use conflicts and capacity constraints. Using the experiences of fisheries successes and failures it is argued only through better governance and institutional change that encompasses the public good of the oceans (biodiversity, ecosystem integrity, sustainability) and societal values (existence, aesthetic and amenity) will fisheries be made sustainable. (c) 2007 Elsevier Ltd. All rights reserved.